The taxonomy’s new clothes: a little more about the DNA-based taxonomy - Santos, Leandro M.; Faria, Luiz R. R. (Zootaxa, 2011)
The use of DNA sequences, including DNA barcoding, as a taxonomical tool has been happening for some time (Tautz et al., 2003; Hajibabaei et al., 2007; Packer et al., 2009). However, the description of new species based solely on DNA sequences is a new idea (Cook et al., 2010) and a new practice (Brower, 2010). Our aim is not to further polarize the war between advocates of strictly molecular or strictly morphological systematics (following, e.g., Pires & Marinoni 2010). The objectives here are (i) to present some arguments regarding the perils of the proposition of a model (theory) for solely DNA-based descriptions (Cook et al. 2010) and the actual publication (practice) of such descriptions (Brower 2010), (ii) to discuss some reasons why we believe that adopting strictly DNA taxonomy for species description, setting aside everything we have learned from classic taxonomy, may not be the best alternative and (iii) to present the point of view about these matters of a PhD candidate and a recently graduated PhD working with taxonomy in a developing country.